SAT0371 Ustekinumab Treatment in Ankylosing Spondylits (AS) Patients Does not Modulate Effector CD4+ T Cell Frequencies Including TH17 Cells. (10th June 2014) - Syrbe, U.; Conrad, K.; Wu, P.; Bacher, P.; Scheffold, A.; Poddubnyy, D.; Sieper, J.
Abstract : Background: Ustekinumab blocks the action of IL-12 and IL-23 by interfering with binding of the p40 subunit to the IL-12Rβ1 subunit used by IL-12 and IL-23 receptors. IL-12 and IL-23 are important cytokines that promote Th1 and Th17 responses. They are produced by monocytes in response to bacterial products such as LPS. Objectives: This study aimed to clarify if therapeutic blockade of p40 modulates frequencies of Th1 and Th17 effector cells and/or if it affects innate responses to LPS. Methods: 20 AS Patients were treated with 90 mg Ustekinumab s.c. at baseline, week 4 and week 16 [1]. Heparinized peripheral venous blood was collected at baseline and at week 24 from these patients and from 20 healthy donors. To determine T effector cell frequencies, we performed in vitro stimulation of whole blood with either phorbol myristate acetate/ionomycin (PMA/I) or with the superantigen SEB for 6 hours with Brefeldin A added after 2 hours. IFNg and TNFa production by CD4+ T cells was determined after intracellular staining and detection by FACS. The frequency of Th17 cells was determined by FACS after enrichment of CD40L+ T cells directly after stimulation according to the method of Bacher et al. [2]. To analyse innate cytokine responses to bacterial stimuli whole blood was mixed with media and incubated with or without LPS for 20 hours. IL-23 and IL-22 (a cytokine induced by IL-23) was detected in the supernatants by ELISA. Results: Ustekinumab treatment did not result in changes of the frequency of Th1 cells according to IFNg or TNFa secretion or in Th17 cells (Table 1 ). In 20h whole blood stimulations we observed elevated spontaneous (w.o. LPS) IL-22 secretion in AS patients at baseline compared to healthy controls. This elevated spontaneous IL-22 secretion decreased upon Ustekinumab treatment (Table 2 ). Also the LPS-induced IL-23 levels were lower after treatment with Ustekinumab at week 24 compared to baseline (p<0.05). Conclusions: Ustekinumab treatment did not affect Th1 or Th17 effector cell frequencies in AS patients. However, reduction of IL-22 and IL-23 production upon Ustekinumab treatment may point to effects rather on innate immune functions. References: Poddubnyy D, Hermann KG, Callhoff J, Listing J, Sieper J: Ustekinumab for the treatment of patients with active ankylosing spondylitis: results of a 28-week, prospective, open-label, proof-of-concept study (TOPAS). Annals of the rheumatic diseases 2014. Bacher P, Schink C, Teutschbein J, Kniemeyer O, Assenmacher M, Brakhage AA, Scheffold A: Antigen-reactive T cell enrichment for direct, high-resolution analysis of the human naive and memory Th cell repertoire. J Immunol 2013, 190(8):3967-3976. Acknowledgements: This study was supported by an unrestricted research grant from Janssen-Cilag. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4729